RASIO KEUANGAN UNTUK MENGUKUR KINERJA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2017-2019 - Arniyatun Febi Hastuti; Istiatin Istiatin; Fithri Setya Marwati (ITB AAS INDONESIA Surakarta, 2021)
Competition in the business world is increasingly competitive, so that companies are required to be able to control business activities better than competing companies. The purpose of this study is to determine the financial performance of telecommunications companies listed on the Indonesia Stock Exchange in terms of financial ratio analysis. The financial ratios used are liquidity ratios, solvability ratio, and profitability ratio. This type of research is qualitative and quantitative research. The research data used is secondary data obtained from the Indonesia Stock Exchange. The results of this study can be seen from the calculation of the liquidity ratio, solvency ratio, and profitability ratio at PT Indosat Tbk, PT XL Axiata Tbk, and PT Smartfren Tbk from 2017-2019 showing poor performance, while the solvency ratio and Net Profit Margin at PT Telekomunikasi Indonesia Tbk is already in good condition. Keywords: Financial Performance; Liquidity; Solvability; Profitability.